Gender stereotype as a vehicle for social change? The case of the Kong Girl. (20th April 2017) - Kang, M. Agnes; Chen, Katherine
Abstract : The Kong Girl stereotype has been circulating in the media since the mid-2000s. The indexical process of associating social meanings to the Kong Girl label becomes heightened in situations of uncertainty and change. Kira Hall uses the term 'indexical dissonance' to explain the state of identity under globalisation. In this paper, we identify three strategies by which more 'positive' representations of Kong Girls emerge: (1) the Kong Girl label shifts in semantic meaning; (2) the specific Kong Girl qualities taken as stance objects shift; and (3) the Kong Girl label is reappropriated. Through these strategies, we show how the meanings associated with a gender stereotype may be co-opted in emerging discourses of social change.